Forensic Staff Attitudes Toward Men Who Have Sexually Offended: A General Public Comparison. Issue 2 (April 2019) - Challinor, Laura; Duff, Simon
ABSTRACT: Objectives: The aim of this study was to explore the attitudes toward men who have sexually offended (MSO) between the general public and professionals and paraprofessionals in forensic settings. Background: Existing research shows a number of different factors that appear to be important in the development, maintenance, and deterioration of attitudes toward MSO. The exploration of such factors requires further exploration. Method: A convenience sample was used for the cross-sectional study. Five hundred fifty-three participants were recruited from the general public and forensic hospitals, both private and National Health Service. An online version of the Attitudes Towards Sex Offenders scale (Hogue, 1993) was distributed via email and social media. Results: Gender was not found to have any impact on the attitudes individuals held toward MSO. The general public was found to have significantly more negative attitudes when compared with those exposed to MSO at work (professional and paraprofessional staff). Duration of employment did not make attitudes any more or less positive. Conclusion: The clinical and societal implications of the research are important for MSO to reduce risk within forensic establishments and be supported to reintegrate successfully into the community. Without the support from both staff and the general public at each stage of rehabilitation, desistance is less likely to be maintained. Research continues to provide varying results regarding the factors that influence the nature of attitudes toward MSO.